Optimization of Chitosan-Carboxymethyl Chitosan Membrane Modification with PVA to Increase Creatinine and Urea Permeation Efficiency - Riska Nurfirda Annisa; Retno Ariadi Lusiana; Gunawan Gunawan; Hasan Muhtar (Jurnal Kimia Sains dan Aplikasi, 2024)
Polyvinyl alcohol (PVA) modified chitosan-carboxymethyl chitosan (CMC) membrane has been successfully fabricated and used as a dialysis membrane. This research aims to examine the manufacturing process, characterization, and dialysis performance of CMC and PVA-modified chitosan membranes. The membrane used the phase inversion method in acetic acid solvent with 5 CS:CMC: PVA dope compositions. Based on FTIR data, the modification process did not produce new spectra. Furthermore, the interaction produces a membrane with higher physical characteristics in terms of porosity, swelling, water uptake, hydrophilicity, and pH resistance values, which increase by 1.5–115%. Meanwhile, chitosan modification makes the membrane structure different from the original, requiring a longer degradation time. The modification also increased the permeation ability of urea by 17–65% and creatinine permeation by 20–62%. Membranes have the ability to be used more than once.